Tibetans exhibit lower hemoglobin concentration and decreased heart response to hypoxia during poikilocapnia at intermediate altitude relative to Han Chinese - Moya, E. A.; Yu, J. J.; Brown, S.; Gu, W.; Lawrence, E. S.; Carlson, R.; Brandes, A.; Wegeng, W.; Amann, K.; McIntosh, S. E.; Powell, F. L.; Simonson, T. S. (Frontiers in Physiology, 2024)
Background. High-altitude populations exhibit distinct cellular, respiratory, and cardiovascular phenotypes, some of which provide adaptive advantages to hypoxic conditions compared to populations with sea-level ancestry. Studies performed in populations with a history of high-altitude residence, such as Tibetans, support the idea that many of these phenotypes may be shaped by genomic features that have been positively selected for throughout generations. We hypothesize that such traits observed in Tibetans at high altitudes also occur in Tibetans living at intermediate altitude, even in the absence of severe sustained hypoxia. Methodology. We studied individuals of high-altitude ancestry (Tibetans, n=17 females; n=12 males) and sea-level ancestry (Han Chinese, n=6 females; n=10 males), both who had been living at ~1300m (~4327ft) for at least 18 months. We measured hemoglobin concentration ([Hb]), hypoxic ventilatory response (HVR), and hypoxic heart rate response (HHRR) with end-tidal CO2 (PETCO2) held constant (isocapnia) or allowed to decrease with hypoxic hyperventilation (poikilocapnia). We also quantified CO2 contribution on ventilation and heart rate by calculating the differences of isocapnic versus poikilocapnic hypoxic conditions (Δ V. I/ΔPETCO2 and ΔHR/ΔPETCO2, respectively). Results. Tibetans had lower [Hb] compared to Han Chinese (p<0.02), consistent with reports for individuals from these populations living at high altitude and sea level. Measurements of ventilation (resting ventilation, HVR, and PETCO2) were similar for both groups. Heart rate responses to hypoxia were similar in both groups during isocapnia; however, HHRR in poikilocapnia was reduced in the Tibetan group (p<0.03), and the calculated heart rate response to CO2 in hypoxia was lower in Tibetans relative to Han Chinese (p<0.01). Conclusion. These results suggest that Tibetans living at intermediate altitude have blunted cardiac responses in the context of hypoxia. Hence, only some of the phenotypes observed in Tibetans living at high altitude are observed in Tibetans living at intermediate altitude. Whereas blunted cardiac responses to hypoxia is revealed at intermediate altitudes, manifestation of other physiological adaptations to high altitude may require exposure to more severe levels of hypoxia.